Landslide susceptibility mapping based on rainfall scenarios: a case study from Sao Paulo in Brazil - Ramos, Leila Maria [UNESP]; Bazzan, Thiago; Motta, Mariana Ferreira Benessiuti [UNESP]; Bernardes, George de Paula [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Amer Inst Mathematical Sciences-aims, 2022)
Mass movement susceptibility mapping from rainfall data and in situ site characterization constitute an important approach for preventing geological-geotechnical accidents on railroads and highways. A comprehensive site characterization program was conducted to identify slopes with mass movements along the 44 km of SP-171 road in the state of Sao Paulo, Brazil. Ninety-two slopes with some degree of instability were found along this section of the road, including rupture scars, active erosive processes and the presence of unstable rock blocks. Two scenarios for mass movement susceptibility (100 mm and 500 mm of accumulated rainfall) were defined by overlaying thematic maps of relief, soil type, geology, accumulated rainfall and declivity using geographic information system-based techniques. The results for both scenarios identified the regions with high and medium susceptibility to mass movements; for the scenario of 100 mm of accumulated rainfall; we found that 27% and 73% of the land area of SP-171 is respectively highly and moderately susceptible to landslide events. For the scenario of 500 mm, we found 58% and 40% to be highly and moderately susceptible areas. This study also allowed us to identify the main geotechnical problems along the 44 km of this road, and thus can be used to guide actions and decisions to avoid or minimize such problems.
Keywords: Geotechnical cartography; GIS; Landslide studies; Susceptibility; Rainfall